Impact of Cu2+ cations substitution on structural, morphological, optical and magnetic properties of Co1-xCuxFe2O4 nanoparticles synthesized by a facile hydrothermal approach - Mohamed, W.S.; Hadia, N.M.A.; Al bakheet, Bashayr; Alzaid, Meshal; Abu-Dief, Ahmed M. (Solid state sciences, 2022)
Spinel ferrites have received extended discussions among different ceramic magnetic nanoparticles due to dependence of its physiochemical properties on the fabrication processes and composition. In this context, copper doped cobalt ferrites (Co1-xCuxFe2O4) with different Cu2+ doping content (i.e., 0.0 ≤ x ≤ 0.4) were successfully fabricated via hydrothermal method. The impact of exchanging divalent cobalt (Co2+) cations by divalent copper (Cu2+) cations on structure-magneto-optic characteristics of Co1-xCuxFe2O4 ceramic magnetic nanoparticles was studied. The spinel single cubic phase of prepared samples with the signature of CuO phase for x ≥ 0.2 was proved by powder X-ray diffraction (XRD) and infrared spectroscopy (IRS) studies. The particle size distribution depending on the Cu2+ doping content was studied by means of XRD and Transmission electron microscopy (TEM) analysis. The particle size is in the range between 11 and 16 nm. The metal-oxygen vibrational modes and the Force constant of spinel structure bonds were investigated using IRS analysis. The optical analysis in the ultraviolet–visible spectrum region by UV–Vis spectroscopy indicates that the optical energy gap of Co1-xCuxFe2O4 nanoparticles range from 1.77 to 2.2 eV. The specific surface area and optical energy gap values of Co1-xCuxFe2O4, demonstrates the possibility of using this compound effectively in water purification processes. The scanning electron microscopy (SEM) and (TEM) analysis confirmed the nano-sized spherical-shaped particle morphology of our investigated nanoparticles. A significant increase in saturation magnetization from 79 to 106 (emu/g) was observed with increase in Cu2+ content from 0.0 to 0.4. Substitution of Co2+ ions in cobalt ferrite lattice structure with Cu2+ ions allow variations in their nanocrystals size, optical energy gap and magnetic characteristics, which has great benefit in using these compounds in many potential applications. [Display omitted] •Single-phase Cu doped cobalt ferrites nanoparticles have been synthesized via hydrothermal method.•Depending on Cu2+ doping ratio, spinel ferrite system exhibits a significant increase in Ms from 79 to 106 (emu/g).•Substitution of Co2+ with Cu2+ ions controls both optical and magnetic properties of Co1-xCuxFe2O4 nanoparticles.